2000
DOI: 10.1210/mend.14.1.0412
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Activation Domain of Human Orphan Growth Hormone (GH) Secretagogue Receptor (GHS-R) Conserved from Pufferfish to Humans

Abstract: Synthetic ligands have been identified that reset and amplify the cycle of pulsatile GH secretion by interacting with the orphan GH-secretagogue receptor (GHS-R). The GHS-R is rhodopsin like, but does not obviously belong to any of the established G protein-coupled receptor (GPCR) subfamilies. We recently characterized the closely related orphan family member, GPR38, as the motilin receptor. A common property of both receptors is that they amplify and sustain pulsatile biological responses in the continued pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 44 publications
1
18
0
4
Order By: Relevance
“…Geris et al [88]reported in chicken, using a perifusion system, that the GH secretagogue L-692, 249 had only 20–25% the in vitro potency of the endogenous releasing factors GHRH and TRH. Recent cloning of a gene in pufferfish (Spheroides nephelus) which shares significant identity to the human GHRP receptor [89]suggests that GHRP may also play an important role in teleosts. Shepherd et al [90]have shown that in tilapia GHRP-2 stimulated GH release in vivo with the same potency as GHRH.…”
Section: Discussionmentioning
confidence: 99%
“…Geris et al [88]reported in chicken, using a perifusion system, that the GH secretagogue L-692, 249 had only 20–25% the in vitro potency of the endogenous releasing factors GHRH and TRH. Recent cloning of a gene in pufferfish (Spheroides nephelus) which shares significant identity to the human GHRP receptor [89]suggests that GHRP may also play an important role in teleosts. Shepherd et al [90]have shown that in tilapia GHRP-2 stimulated GH release in vivo with the same potency as GHRH.…”
Section: Discussionmentioning
confidence: 99%
“…However, although these peptides show high receptor affinity, they are unable to stimulate GH secretion from somatotroph cells (Ghigo et al 2001). This sequence of seven amino acids has been universally conserved among different species from fish and reptiles to birds and mammals (Palyha et al 2000), which suggests that ghrelin has an important physiological significance.…”
Section: Growth Hormone Secretagogue Receptor and Other Receptorsmentioning
confidence: 99%
“…In previous functional studies of the GHS-R in non-mammalian species, artificial ligands such as GHRPs and nonpeptidyl GHSs have been utilized. A GHS-R homologue identified in the pufferfish shares 58% identity to human GHS-R and is activated by GHRP-6 and nonpeptidyl GHSs (17), suggesting that GHS binding to the GHS-R is not species-specific. These GHS species, however, bind relatively weakly to pufferfish, compared with human GHS-R, possibly due to structural differences between the two receptors.…”
Section: Figmentioning
confidence: 99%